2015
DOI: 10.1111/jfpp.12494
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Composition, Color and Nutritional Profile of Raw and Cooked Goose Meat with Different Methods

Abstract: Proximate composition, color and nutritional profile of raw and cooked goose breast and leg meats were investigated. Water, pH, L* value, total saturated fatty acid (SFA), total polyunsaturated fatty acid (PUFA), Ca, K, Mg, P and Zn contents of leg meat were higher than those of breast meat, while protein, fat, a* value, b* value, total monounsaturated fatty acid (MUFA), Na and Fe contents of breast meat were higher than those of leg meat. pH of breast meat increased with cooking, whereas pH of leg meat decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 28 publications
9
48
10
Order By: Relevance
“…However, water is not the only compound lost during the cooking process. There are various components such as myofibrillar and sarcoplasmic proteins, collagen, lipids, salt, polyphosphates and flavour compounds that are also lost together with the water (Oz & Celik, 2015). In the present study, as a result of grilling at different temperatures, cooking losses of the meatballs varied between 40.75 and 49.09% (Table 1).…”
Section: Proximate Analysis and Cooking Lossmentioning
confidence: 56%
See 1 more Smart Citation
“…However, water is not the only compound lost during the cooking process. There are various components such as myofibrillar and sarcoplasmic proteins, collagen, lipids, salt, polyphosphates and flavour compounds that are also lost together with the water (Oz & Celik, 2015). In the present study, as a result of grilling at different temperatures, cooking losses of the meatballs varied between 40.75 and 49.09% (Table 1).…”
Section: Proximate Analysis and Cooking Lossmentioning
confidence: 56%
“…It was previously declared that the increase in pH values by cooking could be attributed to the cleavage of bonds involving imidazole, sulfhydryl and hydroxyl groups (Oz & Celik, 2015). While it was observed that CLA concentrations and temperature had a very significant effect (p < 0.01) on the pH values of the samples, the interaction between concentration and temperature had no significant effect (p > 0.05) on pH values.…”
Section: Proximate Analysis and Cooking Lossmentioning
confidence: 86%
“…In a previous study on chicken meat, it was seen that L * and a * values were decreased, and b * values were increased. A dry heat method such as grilling results in dark colour with a decrease in L * value (Oz & Celik, ). The infrared grilled lamb patties also showed the same decline, which was lesser than for charcoal grilling.…”
Section: Colourmentioning
confidence: 99%
“…Liao, Wang, Xu, and Zhou () reported that the 74.42% water content of raw chicken breast decreased in cooked samples to 53.77 to 69.52% and 76.50% water content of raw duck breast decreased to 52.66 to 69.44% following the cooking process. Oz and Çelik () reported that water contents in raw breast and raw leg meat were 66.38% and 72.43% and after cooking process these values varied between 53.87 to 62.92% and 51.38 to 64.17%, respectively for the corresponding cooked samples depending on cooking methods.…”
Section: Resultsmentioning
confidence: 99%
“…Liao, Wang, Xu, and Zhou (2010) reported that the 74.42% water content of raw chicken breast decreased in cooked samples to 53.77 to 69.52% and 76.50% water content of raw duck breast decreased to 52.66 to 69.44% following the cooking process. Oz and Çelik (2015) reported that water contents in raw breast and raw leg n is the number of samples analyzed. The pH value of the leg meat was found to be higher than that of the breast meat.…”
Section: Water Content and Ph Value Of Cooked Breast And Leg Meatmentioning
confidence: 99%